GREATER TIPRALAND: A MOVEMENT FOR SEPARATE STATEHOOD IN TRIPURA - Debbarma, Triveni (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India, prior to and following gaining independence, has experienced a sequence of popular movements concerning the issue of creating harmony in eco-political and cultural aspects. This is also true for the North East region of India. Following India's independence, Tripura experienced a significant influx of immigrants who established permanent residency. This has engendered feelings of disorientation and dread among diverse ethnic communities inhabiting the area, leading to unsettling occurrences of ethnic turmoil, strife, aggression, and even political separation in various regions of Tripura. Since gaining independence, Tripura has experienced several political and non-political activities aimed at restoring the patriachal and ethnic identity of its tribes. The Tiprasa people are the indigenous inhabitants of Tripura and the northeastern area of India. The presence of their affluent cultural and ethnic components has facilitated the development of a distinct political identity. The party named IPFT created an upstart campaign for Tipraland for the tribal people of Tripura. In 2019, once again, tribes from Tripura initiated a significant campaign advocating for the establishment of an independent territory called "Greater Tipraland". The TIPRA Motha Party has expressed this demand. The primary aim of the article is to examine the historical context of the "Greater Tipraland" movement in Tripura and assess the effectiveness of the Sixth Schedule in the TTAADC region. This paper aims to conduct a thorough investigation into the multiple facets of the "Greater Tipraland" Movement. Hence, it may be inferred that the Greater Tipraland movement is a distinct movement seeking statehood, wherein Tipra Motha advocates for a constitutional resolution within the framework of the Sixth Schedule of the Constitution of India. An intensive discourse and a solid constitutional foundation can effectively address the concerns voiced by the Tiprasa community.